2019
DOI: 10.1186/s12958-019-0515-6
|View full text |Cite
|
Sign up to set email alerts
|

Segmental aneuploidy in human blastocysts: a qualitative and quantitative overview

Abstract: Background Microarray-based and next generation sequencing (NGS) technologies have revealed that segmental aneuploidy is frequently present in human oocytes, cleavage-stage embryos and blastocysts. However, very little research has analyzed the type, size, chromosomal distribution and topography of the chromosomal segments at the different stages of development. Methods This is a retrospective study of 822 PGT-A (preimplantation gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 51 publications
5
32
3
Order By: Relevance
“…It has been reported that approximately ~6-15% of blastocysts from human IVF have segmental abnormalities when evaluated by current PGT-A methods with different analysis platforms [25,27,28]. The incidence of blastocysts with only segmental abnormalities is about 2.4%-7.5% of all samples examined [25,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that approximately ~6-15% of blastocysts from human IVF have segmental abnormalities when evaluated by current PGT-A methods with different analysis platforms [25,27,28]. The incidence of blastocysts with only segmental abnormalities is about 2.4%-7.5% of all samples examined [25,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, DSBs elicit a DNA repair mechanism, and failure to execute it typically activates the apoptotic process [73]. Those pathways are often compromised in preimplantation embryos, which are characterized by rapid cell division, compromised repair mechanisms, lax cell cycle checkpoints, and deregulated apoptosis [74]. When a cell 'repairs' a DSB incorrectly, it can result in duplication or deletion of the segment containing the break.…”
Section: Segmental Abnormalitiesmentioning
confidence: 99%
“…Segmental abnormalities can occur in any chromosome, their incidence across the genome largely correlates with chromosomal size, and the frequency of losses and gains is roughly equal [75]. One possible outlier is the high incidence of segmental gains in the q-arm of chromosome (Chr) 9 [74,75]. A study has described loci in the genome of preimplantation embryos with higher likelihood of segmental abnormalities, possibly related to heterochromatic composition of those regions [70].…”
Section: Segmental Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations